PENGARUH INTEGRITAS DAN KOMPETENSI AUDITOR TERHADAP KUALITAS HASIL PEMERIKSAAN PADA INSPEKTORAT PROVINSI SULAWESI- SELATAN - Nur Fatma Basar (AkMen JURNAL ILMIAH, 2015)
Integrity and Competence Auditor influence on the Quality Examination in South Sulawesi Provincial Inspectorate. This study aimed to analyze the effect of integrity and competence of the auditors on the quality of the examination results on the inspectorate South Sulawesi, and to analyze which variables are dominant. Gathering data using questionnaires distributed to 93 respondents, while questionnaire to restore as much as 73. Of these respondents, there are 42 people or 57.53% aged over 40 years, while the remaining <40 years. Male respondents as many as 48 people or 65.75% and women by 25 people or 34.25%. Working period 1-10 years as many as 33 people or 45.21%, and 55.79% above 10-year tenure. Group III as many as 53 people (72.60%) while the rest of class I, II, and IV. S1 education level as many as 45 people, or approximately 61.64%, while the remainder had high school education, Diploma, and Magister. Training of the most widely followed as much as two times the number of 24 people (32.88%). The results showed that either simultaneously or in partial, Integrity and Competence positive and significant impact on the quality of the results of the Inspectorate of South Sulawesi province. Thus, the first hypothesis is proven research. Of two independent variables used in the quality of the examination, competency variables that have a dominant influence on the quality of the examination results in the Inspectorate of South Sulawesi province. Thus, the second hypothesis of this study is proven.